Humoral and skin mucosal immune parameters, intestinal immune related genes expression and antioxidant defense in rainbow trout (Oncorhynchus mykiss) fed olive (Olea europea L.) waste. Issue 100 (May 2020) - Hoseinifar, Seyed Hossein; Shakouri, Meysam; Yousefi, Samira; Van Doan, Hien; Shafiei, Shafigh; Yousefi, Morteza; Mazandarani, Mohammad; Torfi Mozanzadeh, Mansour; Tulino, Maria Grazia; Faggio, Caterina
Abstract: A six-week feeding trial was carried out to evaluate the effects of inclusion of dietary olive waste cake (OWC, 0, 0.5, 2.5 and 5 g kg −1 diet) on performance, antioxidant condition and immune responses of rainbow trout ( Oncorhynchus mykiss ) (2.5 ± 0.1 g). Supplementing diet with 2.5 and 5 g OWC kg −1 diet significantly enhanced serum and mucosal lysozyme activity in fish. Regarding mucosal immunity, fish fed 2.5 and 5 g OWC kg −1 diets had higher skin mucus total Ig concentrations than other groups. In relation to antioxidant status, those in 2.5 g OWC kg −1 and the control groups exhibited the highest and the least liver superoxide dismutase and glutathione peroxidase activities, respectively. Furthermore, the activity of liver glutathione S transferase in fish fed 2.5 and 5 g OWC kg −1 diets was higher than the other treatments. In respect to gut cytokines gene expression, our findings demonstrated dietary OWC did not influence interlukines-1β and 10 genes expression, but relative expression of IL8 gene gradually up-regulated with increasing dietary OWC level. Moreover, fish fed 0.5 g OWC kg −1 and the control diets had the highest and the lowest gut tumor necrosis factor-α gene expression values, respectively. The relative expression of transforming growth factor-β significantly down-regulated in gut of fish fed 2.5 and 5 g OWC kg −1 diets compared to other groups. Supplementing diet with OWC pronouncedly improved growth and feed conversion ratio in fish compared to the control. Overall, the findings of this study suggested that inclusion of 2.5 g OWC kg −1 diet can improve growth rate, oxidative stress status, humoral and skin mucosal immune responses in O. mykiss fingerlings and it can be considered as a functional feed additive for this species. Highlights: Dietary olive waste cake (OWC) increased serum immune parameters in trout fingerlings. Trout fingerlings fed OWC showed altered mucosal immunity. Feeding on OWC significantly increased the antioxidant enzymes activity. Immune related genes were modulated by supplementing OWC in diet.